POLA KERAPATAN DAN KERAGAMAN TEGAKAN HUTAN DIPTEROKARPA SEKUNDER (Pattern of Density and Diversity of Secondary Dipterocarps Forest Stand) - Farida Herry Susanty (Jurnal Penelitian Hutan Tanaman, 2020)
ABSTRACTThe assessment of dipterocarp secondary forest recovery has important parameters namel stand density and diversity of forest species composition. This study aims to determine trends in patterns of change in density and diversity of secondary dipterocarp stands innatural forests based on variations in logging aged as projections of natural recovery thatoccurs in production natural forests. The study was conducted at the Natural Forest IUPHHK of PT. Gunung Gajah Abadi, Wahau, East Kalimantan. Data collection period on 2016-2019 by building temporary sampling plots of 11 plots (11 hectares) on 7 variations of logging aged. Density parameters (i.e. number of trees and basal area per unit areaand diversity (number of species, heterogeneity index, species abundance and evennessindex) of Dipterocarp secondary forest stands will vary over the logging aged. The form ofthe relationship of stand density, abundance index and species evenness index islogarithmic regression form, while for base field parameter, the number and index ofspecies diversity are polynomial or quadratic regression. Aged stands after logging is factor that influences quite a large number of species composition, but is not large enoughfor other stand density and diversity parameters.                                                            ABSTRAK Penilaian pemulihan hutan sekunder dipterokarpa mempunyai parameter penting, yaitu kerapatan tegakan dan keragaman komposisi jenis hutan. Penelitian ini bertujuan untuk mengetahui kecenderungan pola perubahan kerapatan dan keragaman tegakan pada hutan alam dipterokarpa sekunder berdasarkan variasi umur tebangan sebagai proyeksi tingkat pemulihan (recovery) alami yang terjadi pada hutan alam produksi. Penelitian dilaksanakan di IUPHHK Hutan Alam PT Gunung Gajah Abadi, Wahau, Kalimantan Timur. Periode pengumpulan data pada tahun 2016-2019 dengan pembuatan plot sampling temporer sebanyak 11 plot (seluas 11 ha) pada tujuh variasi umur tebangan. Parameter kerapatan (jumlah pohon dan bidang dasar per satuan luas) dan keragaman (jumlah jenis, indeks keanekaragaman, kelimpahan jenis dan indeks kemerataan jenis) tegakan hutan sekunder dipterokarpa akan bervariasi sepanjang umur tebangan. Bentuk hubungan parameter kerapatan tegakan, indeks kelimpahan dan indeks kemerataan jenis adalah berbentuk regresi logaritma, sedangkan untuk parameter bidang dasar tegakan, jumlah dan indeks keanekaragaman jenis berbentuk regresi polynomial atau kuadratik. Umur tegakan setelah penebangan merupakan faktor yang memengaruhi cukup besar terhadap komposisi jumlah jenis, tetapi tidak cukup besar untuk parameter kerapatan dan keragaman tegakan lainnya.